Study of Some Immunological Parameters with Level of Iron in Women Infected with Trichomonas Vaginalis - Lima Tariq Youash Lazar1 , Kasim Sakran Abass2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Trichomonas vaginalis is a flagellated protozoan parasite that causes a disease called trichomoniasis inhumans. It affects the urogenital tract and is one of the most important causes of non-viral genitourinarysexually transmitted infection (STI). The host’s immune response plays a very important role in the onsetof pathological symptoms and their differences between infected people. During the period from July toDecember 2019, 30 samples were collected, 20 of infected women with T. vaginalis and 10 samples as acontrol group from reviews of external women’s clinics in Kirkuk city, whose ages ranged between 18-56 yearsso this study was designed to know the effect of infection with T. vaginalis parasite on some immunologicalparameters such as the role of humoral immune response based on the production of immunoglobulins IgM,IgG, IgA against the parasite and there estimation in serum by using Enzyme Linked Immunosorbent Assay(ELISA) technique as well as estimating the C-Reactive protein concentration as an indication of systemicinflammation and of serum iron level . The results of the current study showed a “significant” increase inthe level of immunoglobulins IgM, IgG in serum of women infected with T. vaginalis compared to thecontrol group, as the level of IgM (8. 2 ± 2.9 ng/dl), (6.3 ± 0.5 ng/dl) Consequently, at the level (p <0.05),the level of IgG was (8.16 ± 2.20 ng/dl), (6.53 ± 1.69 ng/dl) for the infected women and the control group,respectively. As for the level of IgA, the results showed non-significant increase in the affected womencompared with control group (8.22 ± 3.1 ng/dl), (7.82 ± 2.8 ng/dl), respectively. The results of estimatingthe CRP concentration showed a significant increase in the infected women compared to the control group(5.76± 1.56 mg/dl), (4.61± 0.66 mg/dl), respectively. While the results of measuring the level of iron showeda significant decrease among infected women and the control group (38.79 ±8.23 mg/dl), (93.83± 34.76 mg/dl), respectively. We conclude from the above that infection with T.vaginals stimulates the humoral immuneresponse and affects on immunoglobulins levels, CRP concentration and Iron serum level.